Genomic and darwinian medicine - Salzano, Francisco M (2009)
Genomic and darwinian medicine deal with the application of hereditary and evolutionary principles for the understanding of health and disease. The progress in molecular and bioinformatic knowledge is making possible through a holistic approach to biological phenomena and one aspect of it, host-pathogen coevolution, is discussed with examples of research performed by our group. The search for the etiology of genetic diseases can focus on simple traits with mendelian inheritance or in more complex multifactorial characteristics, as well as in nuclear or mitochondrial DNA genes. Also important is the investigation of genetically conditioned variation in response to drugs (pharmacogenomics) and unorthodox environmental effects (epigenetics). Every day the genome of a given cell receives one million lesions which should be repaired. Defects in repair mechanisms can lead to diseases, one important category of them being neurological disorders. The association between intronic inversions which lead to severe hemophilia A and the prevalence of Factor VIII inhibitors in these patients was also considered using information obtained by the Porto Alegre group and those of colleagues living in other cities. The fi nal message emphasizes the need for an evolutionary approach to fully understand pathologic processes and their management.